2013
DOI: 10.1182/blood-2012-11-466938
|View full text |Cite
|
Sign up to set email alerts
|

Genomic instability may originate from imatinib-refractory chronic myeloid leukemia stem cells

Abstract: • Imatinib does not prevent accumulation of genomic instability in CML-CP.• Imatinib-refractory leukemia stem cells may be a source of genomic instability in CML-CP.Genomic instability is a hallmark of chronic myeloid leukemia in chronic phase (CML-CP) resulting in BCR-ABL1 mutations encoding resistance to tyrosine kinase inhibitors (TKIs) and/or additional chromosomal aberrations leading to disease relapse and/or malignant progression. TKI-naive and TKI-treated leukemia stem cells (LSCs) and leukemia progenit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 54 publications
5
94
0
Order By: Relevance
“…Quiescent and proliferating tumor cells accumulate spontaneous and treatment-induced DSBs, which are eventually repaired and thereby tolerated (18,24,25). Inhibition of DSB repair has emerged as a promising antitumor treatment, especially in the context of synthetic lethality, which targets specific pathways to eradicate tumor cells while sparing normal cells (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quiescent and proliferating tumor cells accumulate spontaneous and treatment-induced DSBs, which are eventually repaired and thereby tolerated (18,24,25). Inhibition of DSB repair has emerged as a promising antitumor treatment, especially in the context of synthetic lethality, which targets specific pathways to eradicate tumor cells while sparing normal cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…CML-CP-like leukemia was characterized by splenomegaly and leukocytosis associated with expansion of mature myeloid cells as described previously (18,19 Microarray analysis. Gene expression data for 15 genes were used to select BRCA/DNA-PK-deficient and -proficient AMLs from a dataset of 172 samples arrayed on an Illumina HT-12 (supplemental data: AML gene expression levels).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quiescent (CFSE max ) and proliferating (CFSE low ) leukemia and normal hematopoietic stem and progenitor cells were detected by flow cytometry using fluorochrome-conjugated anti-Lin, anti-CD34, and anti-CD38 antibodies (BD Pharmingen), as described previously. 10,14 Cell viability was determined by Trypan blue exclusion. Cell death and g-H2AX were measured by flow cytometry using Fixable Viability Dye eFluor 660 (eBioscience) and Alexa Fluor 488 Mouse anti-H2AX (phosphoserine 139) (BD Pharmingen) as described before.…”
Section: In Vitro Treatmentmentioning
confidence: 99%
“…In the IRIS study, patients with low-, intermediate-, or high-risk Sokal's score showed significantly different response rates as 5-year CCyR (89, 82, and 69 %, respectively: P<0.001) and progression to advanced disease (3,8, and 17 %, respectively: P=0.002) [1].…”
Section: Introductionmentioning
confidence: 99%